The discursive construction of foundation programmes in South African media texts - Bernard, Taryn (South African Journal of Higher Education, 2016)
This research investigates public perceptions of transformation within South African universities, with a particular focus on the incorporation of foundation programmes into university curricula. Foundation programmes are an initiative on behalf of both governmental and higher education (HE) institutions to grant wider and equal access to HE. However, it is evident that public views regarding university plans and admission policies are varied and the actions on behalf of both governmental bodies and universities are interpreted in diverse ways. These interpretations are problematic if they are misinformed, yet are able to influence or limit participation in HE. This study utilizes methods developed within critical discourse analysis (CDA) to closely analyse three media texts that articulate various perceptions regarding the changing HE system. In line with Gee’s (1996) model of CDA, these three texts are viewed as individual instances of societal discourses about HE, but also provide insight to ideologies relating to education and access.